Potency of Solar Hydrogen Generation System in Urban Area: Case Study of Bandung City - Pramujo Widiatmoko; Hary Devianto; Isdiriayani Nurdin; Saumi Febrianti Khairunnisa; Muhammad Irfan Rafi (Jurnal Teknologi Bahan dan Barang Teknik, 2016)
Development of hydrogen production system is important in the future to support electric vehicles operation. This paper studies potency of rooftop PV-PEM electrolyser system connected to fuel station in urban area of Bandung City. Rooftop inclination and orientation of the PV influences the generated electricity by 0.8 – 4.2% compared with horizontal installed-PV. With the solar to hydrogen efficiency of 8.5%, we found that the rooftop installed PV-electrolyser system in Bandung City with supporting area with a radius of 500 m is potentially able to provide fuel for up to a hundred vehicles daily. Further, the potency of rooftop solar hydrogen generation was mapped.Pengembangan sistem produksi hidrogen sangat penting untuk mendukung pengoperasian kendaraan listrik di masa depan. Penelitian ini mempelajari potensi dari pemasangan sistem PV-PEM electrolyser yang terhubung dengan stasiun pengisian bahan bakar di area Kota Bandung. Kemiringan atap dan orientasi panel surya mempengaruhi jumlah energi listrik sebesar 0,8 – 4,2% dari panel surya yang dipasang secara horizontal. Dengan efisiensi solar-to-hydrogen sebesar 8,5%, atap perumahan yang terpasang sistem PV-PEM electrolyser di Kota Bandung dalam radius 500 m dapat menyediakan bahan bakar hingga seratus mobil listrik per hari. Penelitian ini mencakup pula pemetaan potensi produksi solar hydrogen di atap perumahan.